Health Promotion Programs, Activities, and Strategies - Yuliana, Yuliana (Journal Health of Indonesian, 2025)
Health promotion is a strategic approach to improving public health through empowerment and sustainable behavioral change. This paper discusses various national health promotion programs in Indonesia, such as Community-Based Health Efforts (UKBM), Alert Villages, Community-Based Total Sanitation (STBM), and Clean and Healthy Living Behaviors (PHBS). The analysis was conducted using a descriptive-qualitative approach by reviewing government policy documents and programs. The results indicate that effective health promotion strategies require synergy between advocacy, community empowerment, health education and communication (KIE), and the reorientation of health services. The conclusion emphasizes the importance of active community participation and cross-sectoral support to achieve sustainable health development goals.